FIQIH HISAB RUKYAH DI INDONESIA (TELAAH SISTEM PENETAPAN AWAL BULAN QAMARIYYAH) - Jaenal Arifin (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
Usually,  in  determining  the  beginning  of  the  Ramadan  and  Shawwal in every year in Indonesia there are always differences that arise due to differences in understanding the fundamental principles that cause by differences understanding of dzahir nash, there is a reference to the opinion on the basis of estimating wujudul Hilal (the moon is exactly on ufuq) and there is also a reference to the opinion of rukyatul hilal (moon is above ufuq with the provisions of Imkanu ar-rukyah), both of the methods in determining the beginning of Ramadan and Shawwal are applied every year in Indonesia. When the results of ijtihad fall on the same day, it does not cause problems in the community, but when the results fall on different days, recognized or not, it certainly can cause problems among the people, especially the ordinary people, at least a little bit of confusion, so they have to wait for government’s decision, in this case the Ministry of Religious Affairs.Keywords: Wujudul Hilal, Ru’yatul Hilal and determination of the beginning of Qamariyah month